Simulations of dolphin kick swimming using smoothed particle hydrodynamics - Cohen, R. C. Z.; Cleary, P. W.; Mason, B. R. (Human Movement Science, 2012)
In competitive human swimming the submerged dolphin kick stroke (underwater undulatory swimming) is utilized after dives and turns. The optimal dolphin kick has a balance between minimizing drag and maximizing thrust while also minimizing the physical exertion required of the swimmer. In this study laser scans of athletes are used to provide realistic swimmer geometries in a single anatomical pose. These are rigged and animated to closely match side-on video footage. Smoothed Particle Hydrodynamics (SPH) fluid simulations are performed to evaluate variants of this swimming stroke technique. This computational approach provides full temporal and spatial information about the flow moving around the deforming swimmer model. The effects of changes in ankle flexibility and stroke frequency are investigated through a parametric study. The results suggest that the net streamwise force on the swimmer is relatively insensitive to ankle flexibility but is strongly dependent on kick frequency.